PROBLEMATIKA WISATA DESA CAFE LAUT SEMARE (CLS) DALAM PRESPEKTIF COLLABORATIVE GOVERNANCE: (Studi Kepemimpinan Kharismatik-Tranformasional) - A'an Warul Ulum; Agus Prianto (Halu Oleo University, 2025)
The research focuses on the collaboration of actors in the development of the Semare Sea Café tourist area in Semare village, employing qualitative methods that examine conditions (history), institutions, leadership, and cooperation processes. This research produces an explanation of the history of the establishment of the Semare Sea Café based on conditions of social conflict and poverty in Semare Village. The initiation of the establishment of the Semare Sea Café still has an impact on pseudo-participation, due to a lack of community involvement and low human resources, which has not accommodated the locality's co-management pattern. The success in the construction of the Semare Sea Café cannot be separated from the role of charismatic local leadership, so that there is a process of the rolling of elites, which has obstacles in sustainability,y as the period of charismatic and transformational leadership becomes an obstacle in sustainability. In order to maximise the collaboration process in the development of the Semare Sea Café (CLS), a review of the sustainability plan is required, optimisation of the government's role in local tourism innovation and synergy with the Private Sector in tourism development in Pasuruan Regency.